Fibrobacter communities in the gastrointestinal tracts of diverse hindgut-fermenting herbivores are distinct from those of the rumen - Neumann, Anthony P. (Environ Microbiol, 2017)
The genus Fibrobacter contains cellulolytic bacteria originally isolated from the rumen. Culture-independent investigations have since identified Fibrobacter populations in gastrointestinal tracts of numerous hindgut-fermenting herbivores, but their physiology is poorly characterized due to few representative axenic cultures. To test the hypothesis that novel Fibrobacter diversity exists in hindgut fermenters, we performed culture and 16S rRNA gene amplicon sequencing on samples collected from phylogenetically diverse herbivorous hosts. Using a unique approach for recovering axenic Fibrobacter cultures, we isolated 45 novel strains from 11 different hosts. Full-length 16S rRNA gene sequencing of these isolates identified nine discrete phylotypes (cutoff = 0.03%) among them, including several that were only isolated from hindgut-fermenting hosts, and four previously unrepresented by axenic cultures. Our phylogenetic analysis indicated that six of the phylotypes are more closely related to previously described subspecies of Fibrobacter succinogenes, while the remaining three were more closely related to F. intestinalis. Culture-independent bacterial community profiling confirmed that most isolates were representative of numerically dominant phylotypes in their respective samples and strengthened the association of certain phylotypes with either ruminants or hindgut-fermenters. Despite considerable phylogenetic diversity observed among the Fibrobacter strains isolated here, phenotypic characterization suggests a conserved specialization for growth on cellulose.